2017
DOI: 10.1007/s00792-016-0908-9
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial level of extremostability of proteins: can they be exploited for protein engineering?

Abstract: Research on extremostable proteins has seen immense growth in the past decade owing to their industrial importance. Basic research of attributes related to extreme-stability requires further exploration. Modern mechanistic approaches to engineer such proteins in vitro will have more impact in industrial biotechnology economy. Developing a priori knowledge about the mechanism behind extreme-stability will nurture better understanding of pathways leading to protein molecular evolution and folding. This review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 231 publications
0
26
0
Order By: Relevance
“…The GC-content variations in all the classes of extremophilic genomes has been deduced by Chakravorty et al . 28 . The study indicates, in spite of the variation observed in each extremophilic class the basis of extreme-stability selection based only on GC-content could be ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…The GC-content variations in all the classes of extremophilic genomes has been deduced by Chakravorty et al . 28 . The study indicates, in spite of the variation observed in each extremophilic class the basis of extreme-stability selection based only on GC-content could be ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Endolysins also can kill susceptible bacteria when applied exogenously as recombinant proteins 2 . The features of endolysins desired for their function as potential novel antimicrobial agents are their high stability and resistance to proteolysis and chemical denaturation 3,4 . As these physical properties are common among enzymes of thermophilic microorganisms, we focused our research on lytic enzymes encoded by bacteriophages thriving in extreme thermophilic environments.…”
Section: Introductionmentioning
confidence: 99%
“…In order to resist the protein unfolding caused by high temperature, thermophilic bacteria have developed special hydrogen bonds that can interact with hydrophobicity. Meanwhile, thermophilic bacterial enzymes are rich in salt bridges and/or extra disulfide bridges to make its structure more stable (Chakravorty et al, 2017). In addition, other thermo-resistance factors, including structural compactness, oligomerization, glycosylation, and hydrophobic interactions between subunits, are crucial for stability (Chakravorty et al, 2017).…”
Section: Defense Mechanism Of Extremophiles Under Various Conditionsmentioning
confidence: 99%
“…Meanwhile, thermophilic bacterial enzymes are rich in salt bridges and/or extra disulfide bridges to make its structure more stable (Chakravorty et al, 2017). In addition, other thermo-resistance factors, including structural compactness, oligomerization, glycosylation, and hydrophobic interactions between subunits, are crucial for stability (Chakravorty et al, 2017). Synthetic biology, including site-directed mutagenesis and directed evolution of enzymes, has been used to improve the thermal stability of target proteins/enzymes, which is essential for their application in bioenergy industry (Adesioye et al, 2018).…”
Section: Defense Mechanism Of Extremophiles Under Various Conditionsmentioning
confidence: 99%